2017
DOI: 10.1002/pssb.201700119
|View full text |Cite
|
Sign up to set email alerts
|

Isomorphic substitution and intermediary energy levels: A new application of DFT modelling and semiconductor theory to describe p-n type junctions interface in heterostructures

Abstract: The ZnO/BaTiO3 heterostructure is a potential alternative for the development of ferroelectric and electronic devices, solar cells and photocatalytic processes. Such system was largely employed and studied, however its interface region is not deeply described in the literature. In this work, a theoretical investigation of the n‐ZnO/p‐BaTiO3 heterostructure was performed based on the DFT/B3LYP calculation level. The results indicate that an isomorphic substitution of atoms occurs between both semiconductor stru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 40 publications
1
4
0
Order By: Relevance
“…At the start, we repeated the original local optimizations of the pure ZnO polytypes on ab initio level, using the CRYSTAL14 code, in order to establish quantitative compatibility with the calculations performed on ZnS and the mixed ZnO/ZnS compounds, for both LDA and HSE functionals. As in the earlier work, we found that the wurtzite polymorph of zinc oxide is the energetically lowest and thermodynamically most stable one, which is in agreement with experimental observations (Liu et al, 2013;Sowa & Ahsbahs, 2006;Kisi & Elcombe, 1989;Bates et al, 1962;Ves et al, 1990;Ö zgü r et al, 2005) and previous calculations (Catlow et al, 2008;Ostapenko et al, 2016;Boulfelfel & Leoni, 2008;Mora-Fonz et al, 2017;Sponza et al, 2015;Jaffe et al, 2000;Wang & Zhang, 2016;Demiroglu et al, 2014;Rasoulkhani et al, 2017;Lacerda & de Lazaro, 2017). As shown in Table S2 in the supporting information, when using LDA, all of the predicted ZnO polytypes (4H, 5H, 6H, 8H, 9R, 12R and 15R), as well as the sphalerite structure, exhibit essentially the same energy as the wurtzite modification.…”
Section: Tablesupporting
confidence: 93%
See 1 more Smart Citation
“…At the start, we repeated the original local optimizations of the pure ZnO polytypes on ab initio level, using the CRYSTAL14 code, in order to establish quantitative compatibility with the calculations performed on ZnS and the mixed ZnO/ZnS compounds, for both LDA and HSE functionals. As in the earlier work, we found that the wurtzite polymorph of zinc oxide is the energetically lowest and thermodynamically most stable one, which is in agreement with experimental observations (Liu et al, 2013;Sowa & Ahsbahs, 2006;Kisi & Elcombe, 1989;Bates et al, 1962;Ves et al, 1990;Ö zgü r et al, 2005) and previous calculations (Catlow et al, 2008;Ostapenko et al, 2016;Boulfelfel & Leoni, 2008;Mora-Fonz et al, 2017;Sponza et al, 2015;Jaffe et al, 2000;Wang & Zhang, 2016;Demiroglu et al, 2014;Rasoulkhani et al, 2017;Lacerda & de Lazaro, 2017). As shown in Table S2 in the supporting information, when using LDA, all of the predicted ZnO polytypes (4H, 5H, 6H, 8H, 9R, 12R and 15R), as well as the sphalerite structure, exhibit essentially the same energy as the wurtzite modification.…”
Section: Tablesupporting
confidence: 93%
“…Although these structures clearly represent polymorphs, the ZnS compound prefers the sphalerite modification in nature, while the wurtzite structure type is the most common one (and presumably also most stable one) in the ZnO system. In addition, various other modifications in the pure ZnO and ZnS systems have been identified theoretically (Catlow et al, 2008;Ostapenko et al, 2016;Sponza et al, 2015;Jaffe et al, 2000;Wang & Zhang, 2016;Milek & Zahn, 2015;Lacerda & de Lazaro, 2017;Sponza et al, 2016;Singh & Tripathi, 2016;Wang et al, 2018) and experimentally (Logar et al, 2009;Bates et al, 1962;Lizandara Pueyo et al, 2010;Tusche et al, 2007;Voggenreiter et al, 2017;Ves et al, 1990).…”
Section: Tablementioning
confidence: 99%
“…In addition, the SH was constructed and optimized with the above-stated parameter (experimental section), as shown in Figure 5C and F. The M-O distances of the constructed heterostructure before and after optimization highlight a different disorder in the structure and all elements, especially oxygen [34,38,39] . This displacement and disorder in oxygen in the heterostructure enhance the charge carriers at the interface, improving the ionic conduction, as speculated elsewhere [34][35][36][37][38][39] . Thus, enhanced DOS in the SH near the Fermi level and BIEF at the interface can be interpreted as the valid reason to boost the transfer rate of charge carriers.…”
Section: Dft Calculations and Durability Analysismentioning
confidence: 58%
“…The PDOS result indicates that the incorporation of Mg into the ZnO lattice causes the creation of additional states with minor defects, which probably points to the existence of oxygen vacancies; however, the overall structure remains in its original state, as shown in Figure 5E [34,35] . Moreover, the incorporation of Mg into ZnO generates additional DOS, which tends to the bands near the Fermi level, resulting in enhanced charge carrier migration among the CB and VB [36,37] . Furthermore, the DOS result is well matched with the experimental result, which shows the reduction of the energy bandgap due to Mg doping in ZnO.…”
Section: Dft Calculations and Durability Analysismentioning
confidence: 99%
“…In aiming to disclose the superior photocatalytic behavior of CuO/ ZnO heterostructure, we propose a DFT-based theoretical Z-scheme to schematically represent the band edge alignment of the CuO/ZnO system, as depicted in Fig. 9, computing the valence and conduction band edge by High-throughput DFT/B1WC calculations as proposed in previous theoretical studies for similar heterostructures [77].…”
Section: Dft Calculationsmentioning
confidence: 99%